In Vitro Susceptibility of Aztreonam-Vaborbactam, Aztreonam-Relebactam and Aztreonam-Avibactam Associations against Metallo-β-Lactamase-Producing Gram-Negative Bacteria - Cécile Emeraud; Sandrine Bernabeu; Laurent Dortet (MDPI AG, 2023)
Background: Despite the availability of new options (ceftazidime-avibactam, imipenem-relebactam, meropenem-vaborbactam and cefiderocol), it is still very difficult to treat infections caused by metallo-β-lactamase (MBLs)-producers resistant to aztreonam. The in vitro efficacy of aztreonam in association with avibactam, vaborbactam or relebactam was evaluated on a collection of MBL-producing Enterobacterales, MBL-producing P. aeruginosa and highly drug-resistant S. maltophilia. Methods: A total of fifty-two non-duplicate MBL-producing Enterobacterales, five MBL-producing P. aeruginosa and five multidrug-resistant S. maltophila isolates were used in this study. The minimum inhibitory concentrations (MICs) of aztreonam, meropenem-vaborbactam and imipenem-relebactam were determined by Etest® (bioMérieux, La Balme-les-Grottes) according to EUCAST recommendations. For aztreonam-avibactam, aztreonam-vaborbactam and aztreonam-relebactam associations, the MICs were determined using Etest® on Mueller-Hinton (MH) agar supplemented with 8 mg/L of avibactam, 8 mg/L of vaborbactam and 4 mg/L of relebactam. The MICs were interpreted according to EUCAST guidelines. Results: The susceptibility rates of aztreonam-avibactam, aztreonam-vaborbactam and aztreonam-relebactam with a standard exposure of aztreonam (1g × 3, IV) were 84.6% (44/52), 55.8% and 34.6% for Enterobacterales and 0% for all combinations for P. aeruginosa and S. maltophila. The susceptibility rates of aztreonam-avibactam, aztreonam-vaborbactam and aztreonam-relebactam with a high exposure of aztreonam (2g × 4, IV) were 92.3%, 78.9% and 57.7% for Enterobacterales, 75%, 60% and 60% for P. aeruginosa and 100%, 100% and 40% for S. maltophila. Conclusions: As previously demonstrated for an aztreonam/ceftazidime-avibactam combination, aztreonam plus imipenem-relebactam and aztreonam plus meropenem-vaborbactam might be useful options, but with potentially lower efficiency, to treat infections caused by aztreonam-non-susceptible MBL-producing Gram-negative strains.